Dissolution of urea phosphate: A kinetic and thermodynamic study by solution calorimetry. Issue 1 (14th September 2022) - Long, Bingwen; Yao, Keke; Zhu, Shijie; Li, ZuHong; Li, Tong; Deng, Fuli; Deng, Hua; Ding, Yigang
Abstract: A thermodynamic and kinetic study of the dissolution properties of urea phosphate (UP) in water is performed using a Calvet type microcalorimeter. Calorimetric measurements reveal the dissolution is endothermic and the heat is perfectly proportional to the amount of UP dissolved, yielding an enthalpy of (33.755 ± 0.65) kJ/mol. By combining the enthalpy data of our measurements and literature, we derive the enthalpies of urea‐phosphoric acid adduct reaction, formation of solid UP and UP dissociation. Dissolution kinetics parameters are estimated using the collected dynamic calorimetric data that are well represented with quasi‐second‐order kinetic model, giving an activation energy of (16.7 ± 2.7) kJ/mol. Thermodynamic modeling of the pH difference between UP and phosphoric acid solutions shows the degree of UP dissociation decreases from 74% to 42% when UP molality increases from 0.02 to 1 mol/kg. Furthermore, the species molality distributions in UP solutions are calculated based on mass balance and the dissociation equilibrium relations considered.